2006
DOI: 10.1016/j.crvi.2006.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Les modalités du cycle sexuel du poulpe Octopus vulgaris du Sud marocain (Tantan, Boujdour)

Abstract: L'étude de la reproduction d'Octopus vulgaris a été réalisée au moyen d'un échantillonnage des débarquements des chalutiers côtiers, opérant entre Tan Tan et Boujdour, de décembre 2001 à mai 2003. L'étude montre que la maturité sexuelle est plus précoce chez les mâles que les femelles. Deux périodes de ponte sont mises en évidence par le suivi du RGS : une ponte printanière de mars à juillet, et une ponte automnale, moins intense, se situant entre septembre et octobre. La multiplication des spermatogonies et d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The start of the winter trips (December 2016 and December 2017) detected very high yields composed mainly of young individuals; this month (December) corresponds to the end of the period of a main recruitment (end of the autumn season). this finding is in agreement with the result of a study carried out by Idrissi et al (2006) on the reproduction of Octopus vulgaris in southern Morocco.In their study, by monitoring the gonado somatic ratio (GSR)they recorded the presence of two spawning periods: an intense spring laying from March to July, and a less intense fall laying between September and October. Another study showed that the laying during July will give rise to high yields of month of November (Sánchez & Obarti, 1993).…”
Section: -Monthly Analysis Of Catchessupporting
confidence: 93%
“…The start of the winter trips (December 2016 and December 2017) detected very high yields composed mainly of young individuals; this month (December) corresponds to the end of the period of a main recruitment (end of the autumn season). this finding is in agreement with the result of a study carried out by Idrissi et al (2006) on the reproduction of Octopus vulgaris in southern Morocco.In their study, by monitoring the gonado somatic ratio (GSR)they recorded the presence of two spawning periods: an intense spring laying from March to July, and a less intense fall laying between September and October. Another study showed that the laying during July will give rise to high yields of month of November (Sánchez & Obarti, 1993).…”
Section: -Monthly Analysis Of Catchessupporting
confidence: 93%
“…The length-weight relationships were similar to those reported for octopuses caught by trawlers in adjacent areas (GUERRA & MANR QUEZ, 1980;QUETGLAS et al, 1998;IDRISSI et al, 2006), showing higher values of the allometric exponent than those reported in studies based on octopuses caught by traps (S NCHEZ & OBARTI, 1993;SILVA et al, 2002;OTERO et al, 2007). Length-weight relationship parameters are dependent on the range of data used (MOREY et al, 2003).…”
Section: Reproduction and Life Historysupporting
confidence: 64%
“…The different types of cells were described in accordance with our microscopic observations, taking into account also the previous histological studies made by Khallahi (2001), Golçalves et al (2002), Khallahi & Inejih (2002), Rodriguez-Rua et al (2005) and Idrissi et al (2006).…”
Section: Methodsmentioning
confidence: 59%